2015
DOI: 10.4236/snl.2015.52004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Organo-Modified Nano Montmorillonite to Protect against the Cumulative Health Risk of Aflatoxin B<sub>1</sub> and Ochratoxin A in Rats

Abstract: The aim of the current study was to prepare organo-modified nano montmorillonite (OMNM) and to evaluate its chemopreventive effects against the hapatonephrotoxicity induced by aflatoxin B1 (AFB1) and ochratoxin A (OA) singly or in combination in rats. OMNM was prepared using Cetyltrimethylammoniumbromide (CTAB) as organic modifier. Eighty male Sprague Dawley were divided into 8 groups and treated for 8 weeks as follow: the control group; the group treated orally with AFB1 (80 µg/kg b.w.); the group treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Herein, the NK mineral induced a significant concentrationdependent decrease in the viability of HepG2 cells for all periods of exposure and media types (with exception of the 6 h treatment in complete medium for both assays). According to our knowledge, no previous studies on HepG2 cell have previously been made with this type of clay and there are still few toxicological studies in the literature about clays with this hepatic cell line (Abdel-Wahhab et al, 2015). Different cytotoxicity studies using clays demonstrated that these minerals are able to cause cytotoxicity in different cell lines, and even induce cell death (Maisanaba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, the NK mineral induced a significant concentrationdependent decrease in the viability of HepG2 cells for all periods of exposure and media types (with exception of the 6 h treatment in complete medium for both assays). According to our knowledge, no previous studies on HepG2 cell have previously been made with this type of clay and there are still few toxicological studies in the literature about clays with this hepatic cell line (Abdel-Wahhab et al, 2015). Different cytotoxicity studies using clays demonstrated that these minerals are able to cause cytotoxicity in different cell lines, and even induce cell death (Maisanaba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a following study with F344 rats, the acute toxicity of AFB 1 (0.25 mg/kg body weight (bw)) in the liver was decreased when OTA (0.5 mg/kg bw) was administered in combination, with no observed toxicity in the kidneys. 77 On the other hand, Abdel-Wahhab et al 78 observed that combination of AFB 1 and OTA caused more pronounced liver and kidney damage and increased oxidative stress in the liver of SD rats than either toxin alone. In the biochemical analysis, parameters related to liver and kidney functions showed synergy when the two mycotoxins were combined.…”
Section: ■ Toxicity Of Combined Mycotoxinsmentioning
confidence: 99%
“…Consumption of certain foods that are reported to provide defence against mycotoxins, such as coffee, strawberries, tea, pepper, grapes, turmeric, fava beans, garlic, cabbage, and onions as well as chemosorbent materials (Abdel-Wahhab, 2000; Abdel-Wahhab and Aly, 2003l Abdel-Wahhab et al, 1998, 1999a, 2005b, 2015b).…”
Section: -mentioning
confidence: 99%